Undetected acute aortic dissection in a patient referred for primary coronary angioplasty: a successful treatment of perioperative bleeding after abciximab administration. (15th December 2010) - Arrivi, A; Tanzilli, G; Tritapepe, L; Mazzesi, G; Mangieri, E
Abstract : The authors describe a case of an acute aortic dissection in a Japanese woman with long-lasting hypertension, who was referred to our cath lab for primary percutaneous coronary intervention because of an ECG feature of acute inferior myocardial infarction and systemic hypotension. A successful treatment of perioperative bleeding followed a missed diagnosis in the early stages and abciximab administration.